Facile synthesis and microwave absorption investigation of activated carbon@Fe3O4 composites in the low frequency band. Issue 41 (25th June 2018) - Yin, Pengfei; Deng, Yu; Zhang, Limin; Li, Ning; Feng, Xing; Wang, Jian; Zhang, Yi
Abstract : Activated carbon@Fe3 O4 composites with good electromagnetic wave absorbing performances in the low frequency range were synthesized via a hydrothermal method. Abstract : Activated carbon@Fe3 O4 composites with good electromagnetic wave absorption performances in the low frequency range were synthesized via the hydrothermal method. The crystal structure, microstructure, magnetization properties, frequency-dependent electromagnetic properties and microwave absorption properties of the as-prepared composites were characterized via XRD, VSM, SEM, TEM and VNA, respectively. The results indicated that the electromagnetic wave absorption performance of the composites can be adjusted through the addition of activated carbon. A suitable loading content of Fe3 O4 NPs on activated carbon can also enhance the microwave absorption performance of the composites. The synergy of dielectric and magnetic loss is the main electromagnetic wave absorption mechanism, and the maximum RL of −10.08 dB at 1.75 GHz with a −5 dB bandwidth over the frequency range of 1.55 GHz (1.07–2.62 GHz) is obtained when the percentage of Fe3 O4 NPs and the thickness of the composites are 74 wt% and 5 mm, respectively. Hence, the composite reported in this study can be used as a promising microwave absorbing material in the low frequency range of 0.5–3 GHz.